Relation between RF noise and gate oxide breakdown location in deep submicron NMOSFETs - Rong Zeng; Wang, Hong (2005 IEEE International Workshop on Radio-Frequency Integration Technology (RFIT): Integrated Circuits for Wideband Comm. and Wireless Sensor Network, 2005)
The relation between the location of gate oxide breakdown in deep submicron MOSFETs and noise characteristics has been studied. RF noise in the frequency range of 2 to 18 GHz of the devices with oxide breakdown at different locations are characterized and compared. The results show that degradation of noise parameter subject to gate oxide breakdown is not only related to breakdown hardness but also the location of the oxide breakdown path. For similar breakdown hardness, formation of the breakdown path closer to source side may result in a larger degradation of device RF noise performance. The physical origin behind oxide breakdown induced RF noise in MOSFETs is investigated. The study provides useful information for the use of MOSFETs for low noise circuits.